Pelatihan Pencatatan Akuntansi Penjualan Melalui Aplikasi Point Of Sales (POS) Pada Umkm Industri Fesyen Di Kota Bandung - Irsan Herlandi Putra; Junaedi Abdillah; Hamidah Hamidah; Muhtarudin Muhtarudin (FKIP, Universitas Palangka Raya, 2024)
Technological developments and competition in the fashion business are increasingly rapid, companies must be able to adapt quickly to changes. Technological transformation is the right step to respond to the changes that occur. Companies and individuals within them are required to carry out digital transformation. The aim of this activity is to provide education and training in order to improve the ability of MSME players in implementing point of sales (POS) applications in one of the fashion companies (clothing lines) in Bandung City, West Java Province. The method used in this training is in the form of a seminar or workshop with 20 participants and is carried out over two days. The main theme in this training activity is to find out the impact of implementing the point of sales (POS) application on sales figures and the impact of implementing the point of sales (POS) application on company profits. Not a few companies have implemented the use of point of sales (POS) applications to be able to adapt to these changes. Digital transformation cannot be done that simply, but requires understanding and how to manage digital transformation effectively. The benefit of research is to provide references and information to stakeholders in the fashion company (clothing line).